GE_GERICHTE P/12983/1999 vom 11. Februar 2013 - GE Cour de justice (2013)
; ORDONNANCE DE CONDAMNATION ; OPPOSITION(PROCÉDURE) ; DROIT TRANSITOIRE ; COMPÉTENCE RATIONE MATERIAE ; EXCUSABILITÉ | CP.260ter; CPP.355; CPP.356; CPP.448; CPP.453; CPP.201; CPP.114